Description of Serum Urea and Creatinine Levels Pre Hemodialysis and Post Hemodialysis at Royal Prima Hospital in Chronic Kidney Disease - Raymond Nazimuddin Putra; Valentine Athania Br Perangin-angin; Sahna Ferdinand; Erny Tandanu (Archives of The Medicine and Case Reports, 2021)
Chronic kidney failure describes as the gradual loss of kidney function and it is irreversible, to replace the loss of kidney function a therapy for kidney function is needed, which is hemodialysis. The objective of this research is to know the levels of urea and creatinine serum for pre hemodialysis and post hemodialysis at Royal Prima General Hospital Medan. The methods that are being used for this research are descriptive with 54 patients as samples. The results of this research loss of urea and creatinine serum levels, with the average urea level for pre hemodialysis being 128.11 mg/dL, and the average urea level for post hemodialysis is 43.26 mg/dL with 1,8% of patient with low urea level, 50% with normal urea level, and 48.2% with high urea level. The average creatine level for pre hemodialysis is 11.56 mg/dL, and the average creatine level is 4.3 mg/dL, with all of the patients still having a high creatinine level. The conclusion is there is a drop in both urea and creatinine serum levels, but the urea level for half of the patients did not go down to normal, and for the creatinine level there are none of the patients’ creatinine levels that go down to normal.